DEMAEX-SIM Simulator latest innovation by Dr. Lee Chia Kuang - Hafizatulazlin, Abdul Aziz; Nur Hartini, Mohd Hatta (2021)
GAMBANG, 15 June 2021 - DEMAEX-SIM or DEMATEL EXCEL Simulator is the latest innovation from a researcher and senior lecturer from the Faculty of Industrial Management, Universiti Malaysia Pahang (UMP), Dr. Lee Chia Kuang, 36.